Quantitative Analysis of Methylated Adenosine Modifications Revealed Increased Levels of N6-Methyladenosine (m6A) and N6,2′-O-Dimethyladenosine (m6Am) in Serum From Colorectal Cancer and Gastric Cancer Patients - Hu, Yiqiu; Fang, Zhihao; Mu, Jiayi; Huang, Yanqin; Zheng, Shu; Yuan, Ying; Guo, Cheng (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer and gastric cancer are the most prevalent gastrointestinal malignancies worldwide, and early detection of these cancers is crucial to reduce the incidence and mortality. RNA methylation plays an important regulatory role in a variety of physiological activities and it has drawn great attention in recent years. Methylated adenosine (A) modifications such as N6-methyladenosine (m6A), N1-methyladenosine (m1A), 2'-O-methyladenosine (Am), N6,2'-O-dimethyladenosine (m6Am) and N6,N6-dimethyladenosine (m62A) are typical epigenetics markers of RNA, and they are closely correlated to various diseases including cancer. Serum is a valuable source of biofluid for biomarker discovery and determination of these adenosine modifications in human serum is desirable since they are emerging biomarkers for detection of diseases. A targeted quantitative analysis method using hydrophilic interaction liquid chromatography-tandem mass spectrometry (HILIC-MS/MS) was developed and utilized to analyze these methylated adenosine modifications in serum samples. The concentration differences between the healthy volunteers and cancer patients were evaluated by Mann-Whitney test, and receiver operator characteristic (ROC) curve analysis was performed to access the potential of these nucleosides as biomarkers. We demonstrated the presence of the m6Am in human serum for the first time, and we successfully quantified the concentrations of A, m6A, m1A and m6Am in serum samples from 99 healthy controls, 51 colorectal cancer patients and 27 gastric cancer patients. We found that the levels of m6A and m6Am in serum were both increased in colorectal cancer or gastric cancer patients, compared to that in healthy controls. These results indicate that m6A and m6Am in serum may act as potential biomarkers for early detection and prognosis of colorectal cancer and gastric cancer. In addition, the present work will stimulate investigations on the effects of adenosine methylation on the initiation and progression of colorectal cancer and gastric cancer.